Electrocatalytic methane direct conversion to methanol in electrolyte of ionic liquid. (20th March 2023) - Jiang, Haomin; Zhang, Luting; Wang, Zhaohui; Han, Zhiwei; Ma, Lixuan; Li, Ang; Sun, Yanzhi; Tang, Yang; Wan, Pingyu; Zhang, Riguang; Chen, Yongmei; Fan, Maohong
Highlights: The electrocatalytic conversion of CH4 to CH3 OH in a non-diaphragm electrochemical bath with ionic liquid [BMIM]BF4 . ·O2 − are generated on ORR cathode while CH4 is activated on Ov-V2 O5 anode, which realize conversion of CH4 to CH3 OH. The average formation rate of 352.5 μ mol gcat −1 h −1 and the Faraday efficiency of 61.1% for CH3 OH are obtained. Abstract: The direct conversion of methane (CH4 ) to methanol (CH3 OH) is of great significance for efficiently utilizing biogas and natural gas, in which the activation of CH4 under mild conditions with high selectivity of CH3 OH in products is challenging. The advantage of electrocatalytic system besides CH4 activation is that could provide active oxygen species in situ. However, whether the sorts of active oxygen species could affect the methane conversion is still unexplored. In this study, a non-diaphragm electrochemical bath with an aprotic ionic liquid [BMIM]BF4 as supporting electrolyte was setup, in which superoxide radicals (·O2 − ) and peroxide anions (O2 2− ) were generated through oxygen reduction reaction (ORR) on cathode while CH4 was activated on anode with a V2 O5 -based catalyst (Ov-V2 O5 ). Methanol and ethanol were identified as the liquid conversion products of CH4, and the average formation rate of 352.5 μ mol gcat −1 h − 1 for CH3 OH with Faraday efficiency of 61.1% were obtained under the optimized conditions. Density function theory (DFT) calculation results suggest that the introduce of V 4+ sites in Ov-V2 O5 enhanced the chemisorption of CH4 molecules on anode surface, and the active oxygen species are involved in the formation of methanol and ethanol. Graphical abstract: Non-diaphragm electrochemical bath with an aprotic ionic liquid [BMIM]BF4 as supporting electrolyte. The synergic effect between the superoxide radicals on the ORR cathode and the anodic catalyst Ov-V2 O5 are essential for the formation of methanol under mild conditions. Image, graphical abstract